KOMPETENSI GURU KELAS PADA SEKOLAH BINAAN DALAM PENYUSUNAN RENCANA PELAKSANAAN PEMBELAJARAN (RPP) BERKARAKTER BERDASARKAN KURIKULUM 2013 MELALUI PENDAMPINGAN DI GUGUS III DAN IV KEC. SELAPARANG TAHUN 2014 - Mir’at, Mir’at (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2015)
This research aims to know the effectiveness of the implementation of assistance in improving teachers’ competency on formulate the character teaching plan, which is useful for supervisors to improve professionalism and for teachers to improve the learning process in the classroom. This study was conducted in two cycles, each cycle twice a meeting. The stages of each cycle are planning, execution, observation, and reflection. The indicators of success in this study are; 1) the results of supervisor observation and teacher observation during the mentoring process has obtained the average score> 4.0, 2) teacher work result in the preparation of character teaching plan reach> 85% with average value> 85.00. The results of the cycle I average of supervisor observation is 3.75 with 58% achievement, average teacher observation is 3.54 with 20% achievement and average individual work result value (77.20 ) with the percentage of achievement (20%). In cycle II the average of supervisor observation is 4,335 with of 100% achievement, the average teacher observation is 4.10 with 90% of achievement and the average individual work result value is 92.29 with 100% of achievement. The success indicator has been reached, the research stated successful and stopped in cycle II. Conclusion; the implementation of assistance can improve the competence of classroom teachers in the target schools in characterized teching plan preparation based on 2013 curriculum. It is recommended that peer supervisors conduct similar research in an effort to improve the competence of targeted teachers, and to other classroom teachers to be able to develop a character teaching plan based on the 2013 curriculum.